Stability and activity of the antimicrobial peptide leg1 in solution and on meat and its optimized generation from chickpea storage protein - Heymich, Marie-Louise; Srirangan, Showmika; Pischetsrieder, Monika (Foods, 2021)
The antimicrobial peptide Leg1 (RIKTVTSFDLPALRFLKL) from chickpea legumin is active against spoilage bacteria, yeast, and mold. The present study tested its effectiveness under food storage conditions and examined options to obtain a food-grade agent. The minimum inhibitory concentration (MIC) of Leg1 against E. coli (62.5 µM) proved stable over seven days at 20◦ C or 4◦ C. It was not influenced by reduced pH (5.0 vs. 6.8), which is relevant in food such as meat. An incubation temperature of 20◦ C vs. 37◦ C reduced the MIC to 15.6/7.8 µM against E. coli/B. subtilis. With a minimum bactericidal concentration in meat of 125/15.6 µM against E. coli/B. subtilis, Leg1 is equivalently effective as nisin and 5000–82,000 times more active than sodium benzoate, potassium sorbate, or sodium nitrite. Replacing the counter-ion trifluoroacetate derived from peptide synthesis by the more natural alternatives acetate or chloride did not impair the activity of Leg1. As an alternative to chemical synthesis, an optimized protocol for chymotryptic hydrolysis was developed, increasing the yield from chickpea legumin by a factor of 30 compared to the standard procedure. The present results indicate that food-grade Leg1 could possibly be applicable for food preservation.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Antimicrobial peptides; Chickpea; Chymotryptic hydrolysis; Counter-ions; Digestion optimization; Leg1; Meat